The effects of inclusion of exogenous phospholipid in Tris diluent containing a different level of egg yolk on the viability of bull spermatozoa - P Situmorang (Jurnal Ilmu Ternak dan Veteriner, 2002)
This study has been conducted to evaluate the effect of inclusion of phospholipid in Tris-diluent containing different level of egg yolk on the viability of bull spermatozoa after chilling and freezing. Semen was collected by means of artificial vagina, diluted in Tris-diluent to get a final concentration 100 x 106 spermatozoa/ml. Diluted semen was cooled to 50C for 45-60 minute, equiliberated in those temperature for 4 hours and frozen by placing the straw 5 cm above surface of liquid nitrogen for 10 minutes. The experiments was factorial designed with two level of phospholipid (0 and 0.5 mm) and 4 concentration of egg yolk (0, 5, 10 and 20% v/v). The viability of spermatozoa was assessed by evaluating the percentage of motile, live and condition of apical ridge after the temperature reduced to 50C, stored at those temperature for 3 and 7 days and after thawing. Inclusion of phospholipid and level of egg yolk in Tris diluent significantly increased the viability of spermatozoa for both chilling and deepfreezing. The mean percentage of motile, live and intact apical ridge for 3 and 7 days of storage times at 50C, were significantly higher (P<0.05) in diluent containing phospholipid than without phospholipid. After thawing, the mean percentage motile, live and intact apical ridges were significantly higher (P<0.05) in a diluent containing phospholipid (49.9; 60.2 and 60.0) than those without phospholipid (39.1; 54.1 and 51.5). The effects of interaction between phospholipid and level of egg yolk on the viability of spermatozoa was not significant for both chilling and freezing. Level of egg yolk significantly (P<0.05) affected the viability of spermatozoa where the optimal level of egg yolk was 10% v/v for chilled semen and the higher level (20% v/v) was needed for frozen semen. In conclusion, Tris diluent containing 0,5 mM phosphatidyl coline with 10 or 20% egg yolk gave a best protection for chilled and frozen semen respectively. Key words: Spermatozoa, viability, phospholipid, egg yolk